Future challenges in the hybrid and improved forage seed markets of East Africa - Florez, Jesus Fernando; Karimi, Peggy; Junca Paredes, John Jairo; Triana Ángel, Natalia; Burkart, Stefan (2024)
In East Africa, forage constitutes a primary food source for dairy cattle. Local forage varieties have traditionally been utilized by producers, but in recent years, there has been a notable surge in the uptake of hybrid and improved forages. These alternatives offer enhanced productivity and greater resilience to climate fluctuations. The fundamental aim of this study is to elucidate the dynamics of the hybrid and improved forage seed market in East Africa within recent years. Additionally, it seeks to construct a forward-looking analysis of the market’s projected evolution over the next decade. Moreover, the study endeavors to pinpoint the central challenges impeding progress and the potential avenues for advancement. Employing a qualitative methodology, we conducted semi-structured interviews with stakeholders along the forage value chains in ten African countries. Our investigation encompassed three core dimensions: i) retrospective analysis of the past decade’s forage market evolution, ii) prospective insights into the market’s trajectory over the ensuing ten years, and iii) identification of obstacles and prospects for improvement. In total, we conducted 46 key informant interviews. Our findings unveiled a virtuous circle that holds the potential to expedite the adoption of (hybrid) forages in East Africa. Research institutions are committed to the continual enhancement of existing varieties and the introduction of novel strains through their breeding and seed selection initiatives. Seed companies are eager to amplify their seed supply. Governments and developmental entities express a vested interest in perpetuating financial support and promotion for the adoption of (hybrid) forages. Collaborative alliances between producer associations and seed companies are on the horizon, aimed at distributing seeds to farmers at more accessible rates. Lastly, dairy farmers exhibit keen interest in (hybrid) forages due to their potential to elevate milk production, optimize cattle farming space utilization, and mitigate susceptibility to climate vagaries